A case of erectile dysfunction induced by red yeast rice in lipid‐lowering therapy. (22nd January 2018) - Liu, Zhigang; Chen, Peijie
Abstract : This paper studies a 39‐year‐old male patient who takes red yeast rice (RYR) for self‐therapy in lipid‐lowering for 3 weeks. Results show that RYR can decrease most of the blood lipid components but without selectivity. During the treatment, the patient developed erectile dysfunction (ED) and accompanied by a dramatic decrease in sexual desire. The ED symptom gradually disappeared within 5 weeks after stopping RYR intake.